2019
DOI: 10.1097/qai.0000000000001998
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana Use Is Not Associated With Changes in Opioid Prescriptions or Pain Severity Among People Living With HIV and Chronic Pain

Abstract: Background: People living with HIV (PLWH) commonly report marijuana use for chronic pain, though there is limited empirical evidence to support its use. There is hope that marijuana may reduce prescription opioid use. Our objective was to investigate whether marijuana use among PLWH who have chronic pain is associated with changes in pain severity and prescribed opioid use (prescribed opioid initiation and discontinuation).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…There is preliminary but promising data to support that medical cannabis initiation can help reduce the opioid dose required to produce pain relief, or substitute the use of opioids altogether, which could help reduce the risk of fatal opioidrelated overdose (Lucas and Walsh, 2017;Reiman et al, 2017;Knerich et al, 2019), although this has not been reported in all studies (Merlin et al, 2019). A cross-sectional retrospective survey reported that medical cannabis use was associated with a 64% decrease in opioid use, improved quality of life, and fewer medication-related side-effects (Boehnke et al, 2016).…”
Section: Cannabinoids With Opioids For Cncpmentioning
confidence: 99%
“…There is preliminary but promising data to support that medical cannabis initiation can help reduce the opioid dose required to produce pain relief, or substitute the use of opioids altogether, which could help reduce the risk of fatal opioidrelated overdose (Lucas and Walsh, 2017;Reiman et al, 2017;Knerich et al, 2019), although this has not been reported in all studies (Merlin et al, 2019). A cross-sectional retrospective survey reported that medical cannabis use was associated with a 64% decrease in opioid use, improved quality of life, and fewer medication-related side-effects (Boehnke et al, 2016).…”
Section: Cannabinoids With Opioids For Cncpmentioning
confidence: 99%
“…Similarly, we thought alcohol may be associated with pain as a recently published qualitative study, Cook et al concluded that PLHIV may engage in risky drinking, in order to manage physical pain [ 41 ]. A similar study by Merlin et al also noted marijuana use was not statistically associated with reductions in pain among PLHIV [ 42 ]. However, studies investigating the associations between marijuana use and pain have reported reductions in pain severity among the general population [ 43 ].…”
Section: Discussionmentioning
confidence: 91%
“…40 Similarly, we thought alcohol may be associated with pain as a recently published qualitative study, Cook et al concluded that PLHIV may engage in risky drinking, in order to manage physical pain. 41 A similar study by Merlin et al also noted marijuana use was not statistically associated with reductions in pain among PLHIV. 42 However, studies investigating the associations between marijuana use and pain have reported reductions in pain severity among the general population.…”
Section: Substance Usementioning
confidence: 85%